2015
DOI: 10.1016/j.gie.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of biliary brush cytology and intraductal biopsy for detection of malignant biliary strictures: a systematic review and meta-analysis

Abstract: Background Evaluation of indeterminate biliary strictures typically involves collection and analysis of tissue or cells. Brush cytology and intraductal biopsies that are routinely performed during ERCP to assess malignant-appearing biliary strictures are limited by relatively low sensitivity. Objective To study the comparative effectiveness of brushings for cytology and intraductal biopsies in the etiology of biliary strictures. Design Meta-analysis. Setting Referral center. Patients PUBMED and Embase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
366
0
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 403 publications
(404 citation statements)
references
References 40 publications
(53 reference statements)
10
366
0
28
Order By: Relevance
“…In this instance, MRI plus magnetic resonance cholangiopancreatography represents the imaging procedure with the highest diagnostic accuracy for localizing and sizing the stricture; thus, the challenge is the definitive demonstration of malignancy [208][209][210][211] . For a definitive diagnosis, these patients usually undergo endoscopic retro grade cholangiopancreatography and a number of procedures (cytology, brushing, FISH (fluorescence in situ hybridization)-polisomy, biopsy, intraductal ultrasono graphy, choledochoscopy, cholangioscopy, chromo endoscopy, confocal endoscopy, narrow-band imaging and so on) can be applied for microscopic confirmation, albeit with unsatisfactory sensitivity [212][213][214][215] . Indeed, at least 40% of patients are sent to surgery without definitive diagnosis and, in 10% of cases after surgery, no evidence of cancer is seen in resected tissues 216 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…In this instance, MRI plus magnetic resonance cholangiopancreatography represents the imaging procedure with the highest diagnostic accuracy for localizing and sizing the stricture; thus, the challenge is the definitive demonstration of malignancy [208][209][210][211] . For a definitive diagnosis, these patients usually undergo endoscopic retro grade cholangiopancreatography and a number of procedures (cytology, brushing, FISH (fluorescence in situ hybridization)-polisomy, biopsy, intraductal ultrasono graphy, choledochoscopy, cholangioscopy, chromo endoscopy, confocal endoscopy, narrow-band imaging and so on) can be applied for microscopic confirmation, albeit with unsatisfactory sensitivity [212][213][214][215] . Indeed, at least 40% of patients are sent to surgery without definitive diagnosis and, in 10% of cases after surgery, no evidence of cancer is seen in resected tissues 216 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…As for iCCA, the risk of tumour seeding after transperitoneal biopsy of pCCA is based on limited evidence 223 . The role of FISH-polisomy in detecting CCA in patients with PSC has been questioned by a meta-analysis, due to its limited sensitivity 215 . Better markers are therefore required for early CCA detection 215 .…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although widely performed, the sensitivity of biliary brush cytology is not sufficiently high, and its accuracy is only 43.0-66.7% [2,3]. The most recent meta-analysis reported that brush cytology for malignant biliary strictures had a sensitivity of 45.0%, specificity of 99.0%, and diagnostic odds ratio (DOR) of 33.43 [3]. Low cellular yields are considered as the primary reason for the low sensitivity of brush cytology.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis determined that transpapillary biopsy for malignant biliary strictures had a sensitivity of 48.1%, specificity of 99.2%, and DOR of 43.18, which were comparable to those of brush cytology [3]. However, combination of brush cytology with transpapillary biopsy increased the sensitivity to 59.4% and the specificity to 100% [3].…”
Section: Introductionmentioning
confidence: 99%